1981
DOI: 10.1111/j.1745-4565.1981.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF THE EFFECTIVENESS OF NOVOBIOCIN ADDED TO TWO AGAR PLATING MEDIA FOR THE ISOLATION OF SALMONELLA FROM FRESH MEAT PRODUCTS

Abstract: Five plating media, Hektoen enteric (HE) and xylose lysine deoxycholate (XLD) agars with and without 80 and 5 μg/ml of novobiocin (N), respectively, and brilliant greeen sulfadiazine (BGS) agar with 80 μg/ml of the antimicrobial agent, were analyzed for the recovery of salmonellae from various fresh beef, pork, and poultry meat products. Of the total Samonella positive samples, 50.0% and 82.5% were found on XLD and XLD‐N agars, respectively, 75.0% and 85.0% on HE and HE‐N agars, respectively and 65.0% on BGS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Both of those studies demonstrated considerably higher recoveries from DSE compared with primary enrichments. Similar to the findings of Hoben et al (1973), Restaino et al (1977), Moats (1978), and Komatsu and Restaino (1981), all of which showed improved Salmonella isolation rates through the use of novobiocin in plating media, the XLDN and BGN media greatly improved the isolation of salmonellae from the present samples and sharply reduced the number of false-negative plating results. Thus, novobiocin contributes to a more-efficient and more-economical system for culturing Salmonella.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Both of those studies demonstrated considerably higher recoveries from DSE compared with primary enrichments. Similar to the findings of Hoben et al (1973), Restaino et al (1977), Moats (1978), and Komatsu and Restaino (1981), all of which showed improved Salmonella isolation rates through the use of novobiocin in plating media, the XLDN and BGN media greatly improved the isolation of salmonellae from the present samples and sharply reduced the number of false-negative plating results. Thus, novobiocin contributes to a more-efficient and more-economical system for culturing Salmonella.…”
Section: Resultssupporting
confidence: 91%
“…Hektoen Enteric agar (HE) with 10 u,g per mL of novobiocin (HEN) still allowed numerous false-positives, caused mostly by colonies of Citrobacter freundii. Komatsu and Restaino (1981) examined the effectiveness of using novobiocin in both XLD and HE for meat and poultry samples and found that for isolating salmonellae, 5 and 80 u.g per mL, respectively, were appropriate media concentrations. There were, however, three times as many false Salmonella-suspect colonies with HEN as with XLDN, even though there were slightly more Salmonella isolations on HEN.…”
Section: Introductionmentioning
confidence: 99%
“…Novobiocin concentrations of 5 to 80 t-Lg/ml have been used with limited success to increase the selectivity of liquid (18,22,34) and solid (19,23,27) media through inhibition of competitive flora, notably Proteus and Citrobacter spp. In the present study, addition of novobiocin (40 t-Lg1 ml) to SC and TBG failed to markedly increase sensitivity of the standard and 6-h standard methods, but apparently compensated for the low selectivity of SC 35 and TBG 35 in direct enrichment (Fig.…”
Section: Resultsmentioning
confidence: 99%